2011
DOI: 10.1007/s10147-011-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of intraluminal brachytherapy in combination with external beam radiotherapy for superficial esophageal cancer

Abstract: There was a clear difference in outcomes of IBT combined with EBRT between mucosal and submucosal esophageal cancers. More intensive treatment should be considered for submucosal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
(45 reference statements)
3
14
1
1
Order By: Relevance
“…Although previous reports showed RT alone was inferior to CRT in esophageal cancer, we did not observe a significant difference in OS between CRT and RT alone [12,14,19,20]. We previously reported the long-term outcome of IBT in combination with EBRT for superficial esophageal cancer [11]. In that report, the most common failure pattern was the primary site, and regional lymph node metastasis tended to occur more frequently in submucosal cases.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Although previous reports showed RT alone was inferior to CRT in esophageal cancer, we did not observe a significant difference in OS between CRT and RT alone [12,14,19,20]. We previously reported the long-term outcome of IBT in combination with EBRT for superficial esophageal cancer [11]. In that report, the most common failure pattern was the primary site, and regional lymph node metastasis tended to occur more frequently in submucosal cases.…”
Section: Discussioncontrasting
confidence: 66%
“…Until 2002, our institution commonly performed intraluminal brachytherapy (IBT) combined with external beam radiotherapy (EBRT) for the treatment of superficial esophageal cancer. We previously reported the long-term treatment results in patients with superficial esophageal cancer who received this treatment [11]. Favorable treatment outcomes in mucosal cancer were achieved in that study.…”
Section: Introductionmentioning
confidence: 89%
“…There was a clear difference in the treatment results depending on the level of tumor invasion; the tumor depth was a significant factor for the overall survival (12). A recent study revealed the correlation between the rate of lymph node metastasis and the depth of the tumor invasion of superficial esophageal cancers.…”
mentioning
confidence: 99%
“…The treatment field and dose of external radiotherapy show variation (13). Additionally, administrations of chemotherapy were different and some studies included data on patients treated with endoluminal brachytherapy or endoscopic submucosal dissection (10)(11)(12)(13). Most of these series involved patients primarily with SCC.…”
Section: Discussionmentioning
confidence: 99%